ANALYSIS OF SOCIOECONOMIC FACTORS ON THE WELFARE OF ELEMENTARY SCHOOL TEACHERS IN DAWAN DISTRICT - I Kadek Widya Segara; Ni Putu Martini Dewi (Adisam Publisher, 2026)
The numerous problems faced by elementary school teachers have the potential to cause dissatisfaction in work activities, which may ultimately affect teacher welfare and performance. Teachers with a high level of welfare tend to work more optimally, whereas low levels of welfare can reduce work motivation. One of the factors assumed to play a role in improving teacher welfare is wages, in addition to the level of education and household consumption. This study aims to analyze the effect of wages, level of education, and household consumption on the welfare of elementary school teachers in Dawan District, Klungkung Regency, both partially and simultaneously. The sample consisted of 62 respondents from 23 elementary schools in Dawan District. The collected data were analyzed using multiple linear regression analysis. The results show that partially, wages, level of education, and household consumption have a positive and significant effect on the welfare of elementary school teachers. Simultaneously, wages, level of education, and household consumption have a significant effect on the welfare of elementary school teachers in Dawan District.